2009
DOI: 10.1111/j.1365-3083.2009.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Effective Method for Dendritic Cell Immunotherapy of Mouse Melanoma

Abstract: Dendritic cell (DC) immunotherapy is a strong candidate for the treatment of incurable cancers especially malignant melanoma. Nevertheless, the proper guideline of DC immunotherapy does not exist. The absence of the guideline is also an obstacle to clinical trials of DC immunotherapy. So we conducted this study in order to develop an effective DC preparation method for immunotherapy in mouse malignant melanoma. Mouse bone marrow‐derived DC were stimulated with tumour antigen alone or tumour antigen plus a cock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…with SWCNT/CpG-2. Mice were sacrificed 48 hours post-treatment and splenocytes were harvested and co-incubated with irradiated (30,000 rad) K-Luc cells for 7 days [ 26 ]. Effectors were then co-incubated for 4 hours with 5,000 51 Cr-loaded K-Luc targets in 96-well plates at ratios of 100:1, 20:1, and 4:1 (nine replicates).…”
Section: Methodsmentioning
confidence: 99%
“…with SWCNT/CpG-2. Mice were sacrificed 48 hours post-treatment and splenocytes were harvested and co-incubated with irradiated (30,000 rad) K-Luc cells for 7 days [ 26 ]. Effectors were then co-incubated for 4 hours with 5,000 51 Cr-loaded K-Luc targets in 96-well plates at ratios of 100:1, 20:1, and 4:1 (nine replicates).…”
Section: Methodsmentioning
confidence: 99%
“…There are many factors other than Tregs depletion to be evaluated and determined in each step of DC-based vaccination in order to standardize and optimize this vaccination treatment 18. Other factors include the source of DC, maturation status of DC, maturation of cocktails, type of antigen, helper antigens, routes of administration, frequency of injections and numbers of injected DCs.…”
Section: Discussionmentioning
confidence: 99%
“…MHC‐I molecules are glycoproteins expressed ubiquitously by most nucleated cells and have been necessary for the presentation of antigens manufactured by these cells to naive CD8 + T lymphocytes (CTL). The published studies in animal models and human clinical trials have confirmed a positive immune response in some tumors, such as renal cancer, melanoma and breast cancer, with DC‐based vaccination strategies 7–12 . But it is still poorly known the relationship between MHC expression alteration and DC‐based vaccine during the therapy process.…”
Section: Introductionmentioning
confidence: 99%
“…The published studies in animal models and human clinical trials have confirmed a positive immune response in some tumors, such as renal cancer, melanoma and breast cancer, with DC-based vaccination strategies. [7][8][9][10][11][12] But it is still poorly known the relationship between MHC expression alteration and DC-based vaccine during the therapy process. In theory, this is of considerable importance to predict DC vaccine efficacy on treatment.…”
Section: Introductionmentioning
confidence: 99%